Dopant-free π-conjugated polymers as hole-transporting materials for stable perovskite solar cells - Pipat Ruankham (2018)
© 2018, Springer Science+Business Media, LLC, part of Springer Nature. Selections of hole transporting materials (HTMs) in perovskite solar cells (PCSs) with conventional structure are crucial for the macroscopic device performance and stability. In this work, four different types of π-conjugated polymers were used as HTMs and the effects of their properties on photovoltaic performance and stability were investigated. It was found that light absorption overlap of HTM with perovskite layer reduces charge generation, implying that HTM also absorbs photon but does not participate in charge generation activity. However, with determination of band alignment, the PSCs with high open circuit voltage (Voc) was achieved with PTB7-TH which has the most appropriate highest occupied molecular orbital level for the valence band edge of the perovskite layer. Finally, in comparison with the as-prepared device, the non-encapsulated PSC with PTB7-TH also showed stable Vocand improved power conversation efficiency upon storing in ambient atmosphere with relative humidity of 55–70% for 112 h.